KOMPARASI DAYA SAING CRUDE PALM OIL (CPO) INDONESIA DAN MALAYSIA DI NEGARA TUJUAN EKSPOR UTAMA - Nurul Elfira; Indra Tjahaya Amir; Sri Widayanti (Fakultas Pertanian, Universitas Janabadra, 2023)
Palm oil is one of the main commodities of the plantation sector which is superior in Indonesia. Palm oil which is processed into Crude Palm Oil has an important role as the largest contributor to foreign exchange in the national economy, namely as a mainstay commodity for non-oil and gas exports. The purpose of this study is to analyze the competitiveness of Indonesian CPO in the main destination countries and to analyze Indonesia's ability to seize the CPO export market. The method used in this study is Revealed Comparative Advantage (RCA) and AR (Acceleration Ratio), using time series data from 1992 to 2021. The results of the study show that Indonesian CPO is highly competitive in India, the Netherlands, China. Indonesia's Crude Palm Oil has a large share of the export market and has a strong position in seizing the export market as indicated by the average value of 1.00